Genuine Conceptualism - Morris, Lynda; Herbert, Anton; Herbert Foundation, Gent (Gent : Herbert Foundation, 2014)
Beuys, Joseph ; Lamelas, David ; Becher, Bernd ; Becher, Hilla ; Gilbert & George ; Huebler, Douglas ; Dibberts, Jan ; Broodthaers, Marcel ; Cadere, André ; Charlton, Alan ; Richter, Gerhard ; et al.
Herbert Foundation, Ghent, July 4 - November 8, 2014
kunstcatalogus